2010
DOI: 10.1097/yic.0b013e328337910b
|View full text |Cite
|
Sign up to set email alerts
|

Loss of response after switching from brand name to generic formulations: three cases and a discussion of key clinical considerations when switching

Abstract: Generic formulations of medications are marketed as therapeutically equivalent and less expensive than branded ones. Multiple studies and case reports have described relapses and worsening clinical outcome in patients after a switch from a brand name to a generic medication. Recent studies have shown that generics do not always lead to the expected costs savings, reducing the impetus to proceed with compulsory generic switching. We report on three patients who experienced clinical deterioration after commencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 13 publications
0
19
0
2
Order By: Relevance
“…Generic switching should be assessed on an individual basis, and with disclosure of possible consequences to the patient and a plan to implement the change and assess its ultimate impact through education and monitoring. 53 …”
Section: Discussionmentioning
confidence: 99%
“…Generic switching should be assessed on an individual basis, and with disclosure of possible consequences to the patient and a plan to implement the change and assess its ultimate impact through education and monitoring. 53 …”
Section: Discussionmentioning
confidence: 99%
“…We also could not examine other changes within the pills, such as changes in the coating or filler, that might accompany changes in color and affect the way that patients with epilepsy perceive their medication. Such changes have anecdotally increased the risk of nonadherence in patients with epilepsy, 47 but not conclusively demonstrated to reflect legitimate differences in the drugs. 48 We limited our definition of nonpersistence to 5 days, although the results were consistent at 10 days, and even such a short break in therapy can be dangerous, particularly for patients with seizure disorders.…”
Section: Commentmentioning
confidence: 99%
“…Interestingly, some studies have shown that the effect of substandard preparations might not be limited to inadequate physicochemical behavior, but can also be extended to influence the clinical outcome of the use of that preparation (Margolese et al, 2010). According to the current regulations issued by the Jordan Food and Drug Administration (JFDA), only random batches of each product are tested after establishing a record for successful testing results for a particular product.…”
Section: Introductionmentioning
confidence: 99%